ntervenções urbanas mediadas pela cultura e os usos dos espaços públicos - Luciana Teixeira Andrade; Clarissa dos Santos Veloso (Ciências Sociais Unisinos)
This paper is focused on urban interventions mediated by culture in large cities. Such inter- ventions aim to promote the cities with economic objectives such as attracting investors, residents and tourists. From an empirical case, the Circuito Cultural Praça da Liberdade, in Belo Horizonte, the changes in sociability at Liberdade Square and the sociocultural limits of this strategy to the urban public life are discussed. The paper discusses the concepts of landscape of power, scene and public space.